Teaching genre-based writing to Korean high school students at a basic level - Lee, Minkyong (My University, 2012)
I will discuss in detail how the genre approach can help Korean students develop their writing proficiency. To do this, I will start with comparing three prominent pedagogies in writing instruction: the genre approach, the product approach, and the process approach. In this section, I will give an overall explanation about what the genre approach is and will discuss the advantages that surpass the product approach and the process approach. In the following section, I will present several definitions of genre to discuss genre-based writing, and I will explain how the genre approach satisfies the requirements of students in EFL settings. In the next section, I will present two supplements for increasing the effect of genre-based writing instruction: scaffolding and collaboration. I will continue to discuss how the procedure of genre-based writing progresses and talk about how to respond to students writing. In the next section, I will show how the genre-based writing theory can be applied to Korean high school situations by introducing a series of lesson plans focused on genre-based writing. I will finish this paper by presenting some areas that need further research for better application of the theory.
Plan B Paper. 2012. Master of Arts-TESOL--University of Wisconsin-River Falls. English Department. ii, 74 leaves. Includes bibliographical references (leaves 62-66).
Keywords: Written communication--Study and teaching (Secondary)--Korea (South); Genre based writing; English language--Study and teaching (Secondary)--Korea (South); Education--Korea (South); Genre; Writing; Literary form--Study and teaching (Secondary)--Korea (South); TESOL